The two frogs and seven other stories: famous animal tales (big book) (Sanjungan Ilusi Kelana Jaya, Selangor, 2010)
"The Two Frogs and Seven Other Stories" is a collection of engaging fables that features various animals and their adventures, each conveying important life lessons. In the titular story, two frogs set out on a journey, facing challenges that test their friendship and resilience. Other stories in the collection introduce a cast of memorable characters, including clever animals who navigate moral dilemmas and learn valuable lessons about cooperation, honesty, and perseverance. With charming narratives and relatable themes, this collection is both entertaining and educational, making it an excellent choice for young readers seeking to understand the values of kindness and teamwork.